THE PROBLEM SOLVING LEARNING MODEL BY USING VIDEO RECORDING ON EXPERIMENTS OF KINEMATICS AND DYNAMICS TO IMPROVE THE STUDENTS COGNITION AND METACOGNITION - Mariati, P. S.; Betty, M. T.; Sehat, S. (Jurnal Pendidikan Fisika Indonesia, 2017)
This research aimed to improve students’s cognition and metacognition through kinematics and dynamics of particle experiment assissted by video recording and tracker software analysis. The research used problem solving learning model which developed using R & D method with 4-D steps, they are define, design, develop, and disseminate. The research involved 86 physics education students academic year 2013/2014 at one of the universities in Medan. The research method is quasi-experimental using randomized control group pretest-posttest design. The experimental class used problem solving learning model assisted by video recording and the control class used direct learning model. The cognition data were collected using multiple-choice test and meta-cognition data were collected using essay test. The students’s cognition and metacognition improvement characterized by the normalized gain score. The research result show that the use of video recording and tracker software analysis was improve the students’ cognition and metacognition in Kinematics and Dynamics topic in moderate category.